Primer registro para Perú de Symmachia sepyra (Hewitson, 1877) (Lepidoptera: Riodinidae) - Cerdeña-Gutierrez, José; Farfan-Larico, Jackie (Instituto de Ecología, A.C., 2015)
Symmachia sepyra (Hewitson) (Lepidoptera: Riodinidae) is reported for the first time in Peru, based on one specimen collected in north of Peru.